Low-carbohydrate diet - application in the treatment of type 2 diabetes - review - Justyna Woźniak; Karol Womperski; Julia Szymonik; Sebastian Szopa; Jagoda Elias (Quality in Sport, 2024)
Introduction: A very low carbohydrate diet called the ketogenic diet has been shown to be effective in the management of drug-resistant epilepsy. In the recent years it has been studied as a potential remedy for conditions such as insulin resistance, type 2 diabetes, obesity, cardiovascular diseases as well as various psychological disorders including drug-resistant depression and schizophrenia. This approach seems to be promising in managing abovementioned issues given a sufficient amount of commitment. There is an abundance of papers looking into the said diet yet not many of them seem to have been well deigned and carried out.